Does Employment Protection Unprotect Workers? The Labor Market Effects of Job Reinstatements in Peru - Bruno Jiménez; Silvio Rendon (Institute of Labor Economics (IZA), 2020)
We investigate the labor market effects of the reestablishment of private-sector workers' right to reinstatement for unfair dismissals, which occurred in 2002 in Peru. Using data from Peruvian Household Surveys from 2004 to 2015, and the Specialized Employment Survey 1998-2001, we estimate a quasi-experimental difference-in-difference model. We find that this reestablishment is associated with increases in new contracting in the private sector, by 5.9 % for permanent hiring and 3.0 % for temporary hiring. By means of placebo tests, we only fund a causal effect of the reinstatement on temporary hiring, not on permanent hiring. We also find a negative association between reinstatements and real wages of 3.9 %, but placebo tests indicate that this is not a causal effect. Our findings call into question the effectiveness of removing reinstatement laws as a policy to increase permanent hiring and wages.
Keywords: J23; J65; E24; 330; labor costs; employment; fixed-term contracts